Obstructive Sleep Apnea and Psychiatric Disorders: A Systematic Review - Gupta, Madhulika A. (J Clin Sleep Med, 2015)
STUDY OBJECTIVES: Obstructive sleep apnea (OSA) has been associated with psychiatric pathology. Psychiatric comorbidity in OSA may affect patient quality of life and adherence to CPAP. A focused evaluation of OSA in highly selected groups of primarily psychiatric patients may provide further insights into the factors contributing to comorbidity of OSA and psychopathology. The goal of this study is to examine the prevalence and treatment of OSA in psychiatric populations. METHODS: A systematic review following the PRISMA guidelines was conducted to determine the prevalence of OSA in schizophrenia and other psychotic disorders, mood disorders, and anxiety disorders, and to examine potential interventions. The PubMed, EMBASE, and PsycINFO databases were searched (last search April 26, 2014) using keywords based on the ICD-9-CM coding for OSA and the DSM-IV-TR diagnostic groups. RESULTS: The search retrieved 48 records concerning studies of OSA in the selected disorders. The prevalence studies indicate that there may be an increased prevalence of OSA in individuals with major depressive disorder (MDD) and posttraumatic stress disorder (PTSD), despite considerable heterogeneity and a high risk of bias. There was insufficient evidence to support increased OSA in schizophrenia and psychotic disorders, bipolar and related disorders, and anxiety disorders other than PTSD. Studies of treatment of OSA indicate an improvement in both OSA and psychiatric symptoms. CPAP adherence was reduced in veterans with PTSD. CONCLUSIONS: OSA prevalence may be increased in MDD and PTSD. In individuals with OSA and psychiatric illness, treatment of both disorders should be considered for optimal treatment outcomes. CITATION: Gupta MA, Simpson FC. Obstructive sleep apnea and psychiatric disorders: a systematic review. J Clin Sleep Med 2015;11(2):165–175.